'Everyone is a Possibility': Messy Networks of Refugees from Syria in Urfa, Turkey. Issue 2 (4th March 2021) - van Uden, Judith; Jongerden, Joost
ABSTRACT: Of the millions of Syrians who have fled their homes since the outbreak of civil war in Syria in 2011, some 3.4 million are registered in Turkey. Although the Turkish government and humanitarian organizations provide services and aid, these do not meet the needs of refugees to ensure their livelihoods. Research indicates that refugees build their livelihoods more upon informal support systems and personal choices than on formal support from the government and humanitarian organizations. Based on a case study in Urfa, Turkey, and using a qualitative approach, this study examines the nature and role of social networks among refugees from Syria and the roles they play. A wide diversity of partly overlapping networks are observed and no single, overarching Syrian community. This study also shows these social networks to be messy, in that they overlap and vary in their dynamics, diversity, and socio-spatial range. This messy nature of networks enables individual refugees to act on possibilities.